Media Sosial Dan Kesehatan Mental Generasi Z - Irwan Budiana (Prosiding Seminar Nasional Ilmu Kesehatan dan Keperawatan, 2024)
The rapid development of technology can certainly affect the lives of generation Z. Current technology has a negative impact on human life. Objective: To describe several research results on the use of social media and mental health of generation Z. Method: The method used in this writing is a literature review which is a systematic, explicit and reproducible method for identifying, evaluating and synthesizing research works and the results of ideas that have been produced by researchers and practitioners. Results: The duration of social media use turns out to have an effect on mental health. Zhao & Zhou (2020) stated that higher social media use is associated with worse mental health. Research such as Bashir & Bhat (2017) suggests several mental illness problems related to the use of social media, including stress, anxiety, depression and loneliness. Research by Heri et al (2021) shows that there is a positive correlation between the intensity of social media use and stress levels. The American College Health Association (2011) found that approximately 30% of college students reported feeling depressed due to social media use. Research in Wuhan, China in 2020 by Gao, showed the impact of social media use on mental health by finding a prevalence of depression of 48%, anxiety of 23%, and a combination of depression and anxiety of 18%. Conclusion: social media can have positive and negative impacts depending on its use, and what we now know is that most social media users, almost all social media users, have an impact on health, especially mental health, on generation Z.